The Bo Xilai Trial and China’s Struggle With the Rule of Law - Ben Self (Washington University Global Studies Law Review, 2015)
This Note will examine the trial of former Chinese politician Bo Xilai and assess whether his trial (the Bo trial) is indicative of a strengthening commitment of China towards some form of the rule of law. Although Bo received more legal protections in his trial than many defendants ordinarily receive in criminal trials, this Note will argue that his case is not indicative of a larger victory for the rule of law in China for two reasons. First, the trial itself was full of a number of procedural irregularities that suggest Bo was deprived of the full protections he was entitled to under Chinese law. Second, even viewing the Bo case optimistically, the case was likely an outlier in terms of Chinese criminal trials generally, as indicated by recent government crackdowns on perceived political dissenters. In analyzing the Bo trial, this Note will attempt to divorce its rule of law analysis from political conceptions that underlie a “thick” version of the rule of law and instead focus only on whether it may be said the Bo trial signals progress towards a “thin” version of the rule of law, a distinction that will be discussed in greater detail in Part III.
Keywords: Bo Xilai; China; rule of law; criminal procedure; Chinese politics; criminal process; defendant; protection